Why Do Publicly Funded Firms Find the University More Useful to Innovate Than Others? Can We Accomplish the RIS3 Target? - Costa, Joana (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
The failure of the deterritorialised innovation policy addressing the regions based on the “one-size-fits-all” policymaking made the Research and Innovation Strategies for Smart Specialisation (RIS3) become the Holy Grail of the European cohesion. This policy strategy is part of a multilevel framework, which encompasses national and regional vectors harmonising transversal strategies and combining different aspects to generate a consistent policy mix. This growth strategy will reinforce the existence of an innovative and knowledge-based society, which aims to raise welfare, promote responsible practices, modernise economic activity and spread prosperity.Sustainable growth will optimise the use of resources, boost the efficiency levels, generate competitiveness and respect the environment. Inclusive growth will promote social and territorial cohesion which is sought after in the convergence policy, which has slowed down the pace after the financial crisis.The development of regional competitive advantages will rely on the establishment of relevant linkages between the Academia and the private institutions in knowledge creation and transfer. In this vein, the University is expected to play a central role, facing important challenges and requiring transformations, mostly in the case of less favoured regions.Productivity raise, construction of comparative advantages, market consolidation and profit maximisation, required to avoid the obsolescence of firms, will rely in the prosecution of innovative activities. Despite being risky, these activities are sought by firms as a source of economic performance increase, being the building blocks of a profit maximisation strategy. The velocity at which innovation occurs will differ among industrial sectors due to their singularities along with other firm structural characteristics, still, those who perform innovative activities are more prone to achieve higher standards of turnover growth and profits. The organisational competences concerning human capital, knowledge absorption, accumulation and diffusion will enhance the innovation capabilities, thus generating advantages. In this path, Universities will be determinant as they may leverage the success of the entrepreneurial innovativeness throughout the provision of relevant knowledge, productive techniques and methods. Absorbing, transforming and exploiting the general knowledge provided by the University will be the firms’ incumbency which will reflect the speed and the success of the individual’s innovative performance. Considering the reinforced role of the Academia as a knowledge producer and therefore inside the innovation process, the existence of incipient connections with firms will be unbearable.What enables and hinders University-firm linkages is, so far, overlooked in the literature demanding for the comprehensive analysis, in particular the causes of its failure, and the accurate policy mix that overcome the situation is vital for a successful RIS3.The singularities of this policy framework require redirection of the tools and actions to be taken such as incentives, grants, loans and subsidisation strategies. Empirical results shed light to the significant difference observed in the classification of the University as a source of information for innovation between public monies recipients and other firms. Among public funding beneficiaries, the Academia is an important source of knowledge to draw upon; conversely, for the other firms, it seems of poor importance the knowledge conveyed in the contact. In general, firms fail to consider the University as a relevant source of information for innovation, which seems to be incompatible with the establishment of smart specialisation strategies.These unexplored connections, which pledge the success of the present innovation policy, and reinforce the importance of its appraisal to fully understand the determinants of University-firm linkages and its connection to public subsidisation, encompassing the identification of the most effective beneficiaries. The econometric estimations, relying on the CIS, were run considering a panel of firms operating in Portugal, which provides the empirical evidence for a moderate innovation milieu which is poorly done so far as most of the studies focus on innovation leader.The findings reinforce the existence complementarities among policy instruments and highlight that new avenues of research should explore other policy instruments such as open innovation frameworks.
Keywords: Europe; Idéation, dialogue et maillage; Innovation ouverte; Réservé UdeM

Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université

Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université